Avifauna Community in Timber Production Area in Segaliud-Lokan Forest Reserve, Sabah - Woon-Jah Lee; Jephte Sompud; Kurtis Jai-Chyi Pei; Mahmud Sudin; Collin Goh; Paul Liau; Fadzil Yahya; Abdul Jalal Sampurai Abdullah (2018)
Selective logging is one of the widespread human activities in tropical forest. It is a recommended forest operation method as opposed to clear-cut logging which has lower impact on environment. Timber production forests that are managed sustainably may acts as potential refuges for avian population. Therefore, the purpose of this study is to present the avifauna community in timber production area of a production forest. The study was conducted from October to December 2017 at Segaliud-Lokan Forest Reserve (SLFR). Two types of surveys were conducted, i.e. bird survey and vegetation survey. Standard point count method was used to conduct bird survey from 0700 hours to 1130 hours. For vegetation survey, 20m x 20 m plot was established on each point count stations. The data was analyzed by descriptive analysis and statistics analysis. Fisher’s alpha diversity index was calculated for the bird species diversity. A total of 55 species with 27 families (228 individuals) were recorded. The value of Fisher’s alpha index of diversity was 23.02. The results show that the avian community in SLFR was similar as compared to other past studies that were logged 20 years ago in Malaysia.